Communication in our lives - Wood, Julia T. (Cengage Learning, 2018)
Communication in our lives, 8th Edition, gives students what they need to strengthen interpersonal, group, public speaking, and media literacy skills. Award-winning scholar Julia T. Wood combines skills development with the latest research and theory of communication scholars. Praised by instructors and students, this product features a highly readable style and Student Voice sections. This edition integrates social and cultural diversity, emphasizes public speaking, expands coverage of mass and social media, and includes a new focus on health communication. Online study tools allow you to customize the content and help your students become more confident and effective communicators.